Prolonged QRS duration as a predictor of right ventricular dysfunction after balloon pulmonary angioplasty. (1st April 2019) - Asano, Ryotaro; Ogo, Takeshi; Ohta-Ogo, Keiko; Fukui, Shigefumi; Tsuji, Akihiro; Ueda, Jin; Konagai, Nao; Fukuda, Tetsuya; Morita, Yoshiaki; Noguchi, Teruo; Kusano, Kengo; Anzai, Toshihisa; et al.
Abstract: Background: Balloon pulmonary angioplasty (BPA) has shown beneficial effects for chronic thromboembolic pulmonary hypertension (CTEPH). However, previous studies have shown less cardiac output improvement and symptoms remaining after BPA, implying poor right ventricular (RV) function recovery. Therefore, we investigated the residual RV dysfunction after BPA to reveal risk factors, clinical effects, and possible underlying histopathological mechanisms. Methods and results: We investigated 61 consecutive CTEPH patients who underwent cardiovascular magnetic resonance before and 3 and 12 months after BPA series. Residual dysfunction (RD) of RV was defined as RV end-diastolic volume index >100 ml/m 2 or RV ejection fraction (EF) <45% at 12-month follow-up. Patients were divided into RD (44%) and normalized dysfunction (ND) (56%) groups. Compared with the ND group, the RD group had significantly worse World Health Organization (WHO) functional class at follow-up. No significant hemodynamic differences were observed between the groups. On multivariable logistic regression analysis, male sex (odds ratio [OR] 12.5, p = 0.004) and prolonged QRS duration (OR 1.08, p = 0.029) were independently associated with residual RV dysfunction. Additionally, RV histopathology in 11 CTEPH autopsy cases showed that QRS duration was correlated with RV fibrosis area. Conclusions: Relatively high percentage (44%) of residual RV dysfunction with worse WHO functional class was observed in CTEPH patients even after BPA. Prolonged QRS duration may predict poor recovery in RV function after BPA. Highlights: Residual right ventricular dysfunction after balloon pulmonary angioplasty was studied. CMR image was obtained at baseline, and 3-month and 12-month follow up after BPA. High percentage of residual RV dysfunction with worse WHO-functional class was observed. Male sex and prolonged QRS duration were associated with residual RV dysfunction. In 11 CTEPH autopsy cases, QRS duration was correlated with RV fibrosis area.